Beyond Disease Intervention: Exploring an Expanded Role for Partner Services in the MATRix-NC Demonstration Project. Issue 2 (February 2022) - Hurt, Christopher B.; Morrison, Arianne S.; Guy, Jalila; Mobley, Victoria L.; Dennis, Ann M.; Barrington, Clare; Samoff, Erika; Hightow-Weidman, Lisa B.; McNeil, Candice J.; Carry, Monique G.; Hogben, Matthew; Seña, Arlene C.
Abstract : Background: Disease intervention specialists (DIS) provide partner services for sexually transmitted infections (STIs). We assessed an expansion of DIS services for clients with HIV and/or syphilis, and contacts within their social and sexual networks. Methods: Black and Latinx cisgender men and transgender women who have sex with men diagnosed with HIV and/or syphilis in 4 urban North Carolina counties were referred to designated DIS, who were trained to recruit clients as "seeds" for chain-referral sampling of sociosexual network "peers." All received HIV/STI testing and care; referrals for preexposure prophylaxis (PrEP) and social, behavioral, and non-STI medical services were offered. Participants completed baseline, 1-month, and 3-month computerized surveys. Results: Of 213 cases referred to DIS from May 2018 to February 2020, 42 seeds (25 with syphilis, 17 with HIV) and 50 peers participated. Median age was 27 years; 93% were Black and 86% were cisgender men. Most peers came from seeds' social networks: 66% were friends, 20% were relatives, and 38% were cisgender women. Incomes were low, 41% were uninsured, and 10% experienced recent homelessness. More seeds than peers had baseline PrEP awareness; attitudes were favorable, but utilization was poor. Thirty-seven participants were referred for PrEP 50 times; 17 (46%) accessed PrEP by month 3. Thirty-nine participants received 129 non-PrEP referrals, most commonly for housing assistance, primary care, Medicaid navigation, and food insecurity. Conclusions: Chain-referral sampling from partner services clients allowed DIS to access persons with significant medical and social service needs, demonstrating that DIS can support marginalized communities beyond STI intervention. Abstract : This CDC-funded project demonstrated that disease intervention specialists could help connect marginalized communities to systems and services supporting their well-being, if the partner services concept is expanded beyond disease intervention.Supplemental digital content is available in the text.